Wormian bones - a case report of post-mortem examination - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
Skull bones provide attachment to numerous facial expressions. Sometimes, as an anatomical variant, small irregular bones (ossicles) appear in the area already present and located at the seams of the cranial skull. These asymmetrical bones are also called sutural bones, which usually occur along the sutures. The observational study concerns bone material located in the Department of Anatomy of the Jan Kochanowski University in Kielce. During the analysis of human skulls, the occurrence of additional bones within the cranial sutures was observed. Morphologically, these bones have different shapes (oval, oblong, round, quadrilateral, polygonal, triangular) and sizes. Wormian bones are more common in the human skull than previously reported, therefore doctors or radiologists should know about this anatomical variant not to confuse it with the clinical aspect during surgery or imaging the skull.